2009
DOI: 10.1007/s10669-009-9218-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of industrial air pollutants on some biochemical parameters and yield in wheat and mustard plants

Abstract: The present study was carried out to determine the impacts of SO 2 , NO x , SPM and RSPM, the most common air pollutants, generated mainly due to industries and vehicles, on some biochemical parameters and yield in wheat and mustard plants during 2006. The concentration of SO 2 , NO x , SPM and RSPM was determined at the polluted sites across the seasons, which ranged between 14. 29-18.10, 20.81-22.43, 483.65-500.85 and 160.67-171.18 lg m -3 , respectively. The wheat and mustard plants grown at polluted sites … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(31 citation statements)
references
References 26 publications
1
27
0
Order By: Relevance
“…Therefore, such plants are the priceless gifts of nature that should be utilized wisely and preserved for future as well (D'Souza et al, 2010). Leaves and exposed parts of plant act as persistent absorber, which provide large surface area for accumulation and absorption to air pollution (Joshi et al, 2009). The plantation in such polluted industrial areas is site explicit activities of tolerance level of plants to oil and gas pollution (Das & Prasad, 2010;Sen et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, such plants are the priceless gifts of nature that should be utilized wisely and preserved for future as well (D'Souza et al, 2010). Leaves and exposed parts of plant act as persistent absorber, which provide large surface area for accumulation and absorption to air pollution (Joshi et al, 2009). The plantation in such polluted industrial areas is site explicit activities of tolerance level of plants to oil and gas pollution (Das & Prasad, 2010;Sen et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Katiyar and Dubey [54] point out that depending on the plant species, leaf age, level of pollution to which are exposed, and also of other biotic and abiotic conditions, chlorophyll content of plants will vary from species to species. Various studies have reported that some air pollutants can reduce chlorophyll content [55][56][57], whereas other pollutants can increase it [14,58]. The chlorophyll signature can be observed in the spectra of all samples maintained in clean environment.…”
Section: Resultsmentioning
confidence: 99%
“…Joshi and Swami (2007) and Seyyednejad and Koochak (2011) reported significant reduction in carotenoid content of different plants grown at polluted sites. Several researchers have reported reduced carotenoid content under air pollution (Joshi et al, 2009;Tiwari et al, 2006). Saquib et al (2010) reported that the root biomass and chlorophyll a showed maximum reduction than any other selected parameters studied in the stressed area.…”
Section: Introductionmentioning
confidence: 96%
“…Chlorophyll measurement is an important tool to evaluate the effects of air pollutants on plants (Joshi et al, 2009), since it plays an important role in plant metabolism and the reduction in of it corresponds directly to plant growth. Abbasi, et al, (2004) and Tripathi, et al (2009) reported that chlorophyll content of plants varies from species to species; age of the leaf and also with the pollution level as well as with other biotic and a biotic conditions.…”
Section: Introductionmentioning
confidence: 99%